Extensive skeletal lesions in childhood acute lymphoblastic leukemia - Hafiz, Md Golam; Islam, A (Mymensingh Medical Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Mymensingh Med J. 2009 Jan;18(1):88-94. The abstract of this article is available on the PubMed website